Streamline density and lesion volume reveal a postero–anterior gradient of corpus callosum damage in multiple sclerosis. (8th April 2020) - Petracca, M.; Schiavi, S.; Battocchio, M.; El Mendili, M. M.; Fleysher, L.; Daducci, A.; Inglese, M.
Abstract : Background and purpose: Although interhemispheric disconnection significantly contributes to disability in multiple sclerosis (MS), the topography, timeline and relationship of callosal damage accrual with hemispheric damage are still unclear. Methods: Streamline density and the presence of focal lesions in five callosal subregions were computed in 55 people with MS [13 relapsing–remitting (RRMS), 20 secondary progressive (SPMS), 22 primary progressive (PPMS)] and 24 healthy controls. Results: Streamline density decrease was identified in SPMS in all corpus callosum (CC) subregions, in PPMS in the posterior CC and mid‐posterior CC and in RRMS in the posterior CC. CC density was independently predicted by CC lesion volume and hemispheric lesion volume and independently predicted visuospatial memory, Expanded Disability Status Scale, manual dexterity and ambulation. Conclusions: The reduction in CC density across phenotypes suggests an earlier involvement of the posterior regions, followed only at a later stage by involvement of the anterior portions of the CC. Such interhemispheric disconnection seems to develop as a consequence of white matter macroscopic damage and exerts a relevant impact on motor and, to a lesser extent, cognitive disability.